(3GdeMUhd aj Yde GdCUhds - (3GdCYQLj, GdMSjfj, GdcGXej, eMSf Hf MSf Hf GdeQJVi, J(B1227(3g`s ((3eMeO Sdje Hf egOjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO agPG gh GdeMUhd aj Yde GdCUhd(B... (3hgh jTJed Ydi NeSI CHhGHs
(3BNQgG (B:s
(3HNdGa GdCUhd aGdCOdI YdjgG edbGI aj GdWQbGJ hGdfGS ajgG(B... (3Ydi feW hGMO hefg jYQa GdLhGH(B... (3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B19s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B6s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B19s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B6s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs